Little Richard : I am everything [videorecording (DVD)] - Little Richard, 1932-2020; Porter, Billy; Jagger, Mick; Waters, John, 1946-; Boone, Pat; McCartney, Paul; Rodgers, Nile; Jones, Tom, 1940-; Hendryx, Nona (Magnolia Home Entertainment, 2023)
"Little Richard: I Am Everything tells the story of the Black queer origins of rock n' roll, exploding the whitewashed canon of American pop music to reveal the innovator--the originator--Richard Penniman. Through a wealth of archival footage, performances, and interviews, the film unspools the icon's life story with all its switchbacks and contradictions." --container.